A “cool-water”, non-tropical, mixed volcaniclastic-carbonate ramp from the Early Cretaceous of southern Chile (45°40’S) - Rivas, Hermann; Salazar Soto, Christian; Stinnesbeck, Wolfgang (Facies, 2023)
The Aysén-Río Mayo Basin was a back-arc/marginal basin developed in southwestern South America (43°-47°S) between the Tithonian-Aptian. Its sedimentary fill corresponds to the Coyhaique Group, which represents a transgressive-regressive succession. Six lithofacies and five microfacies were defined for three outcrops exposed south of Coyhaique (45°40’S). The outcrops have a mixed calcareous-volcaniclastic composition and were assigned to the early transgressive Toqui Formation, i.e., lowermost part of the Coyhaique Group. These mixed rocks comprise bioclastic-volcaniclastic conglomerate, gravelly allochemic sandstone, and gravelly-sandy allochem limestone. Bedding is sharp to amalgamated, sometimes rippled, depicting a wave- and storm-influenced, mixed inner- to mid-ramp. The ramp developed over a Valanginian, active volcanic terrain (Foitzick Volcanic Complex), source of the volcaniclastic sediments. Limestones are rich in reworked bioclasts, and controlled by calcitic organisms including gryphaeid oysters, non-geniculate red algae, and echinoid fragments, defining a heterozoan association (“maerl”-like sediments); less frequent are ahermatypic corals, serpulids, and carbonized wood. Based on their inferred paleolatitude (south of 45°-50°S), fossil assemblage (heterozoan), and kind of carbonate platform (ramp-type), these calcareous rocks of the Toqui Formation depict a “cool-water” (sensu lato), non-tropical setting. The fossil assemblage includes oysters (Aetostreon spp.), and abundant calcareous red algae attributed to Archamphiroa jurassica Steinmann (1930), a taxon previously known from the upper Tithonian Cotidiano Formation of Argentina. A. jurassica is here reported for the first time for the Lower Cretaceous of Chile, suggesting a broader upper Tithonian—Valanginian-Hauterivian? range for the species. The facies model presented here contrasts with the depositional environments depicted for correlative reefal rocks in Argentina (Tres Lagunas Formation), which reflect a “warm-water” setting. In the Aysén-Río Mayo Basin, the influence of sea-water key physical variables in the carbonate sedimentation, as well as the position and hydraulic regime of the carbonate platforms within the basin, and their interaction with the volcanism are still unclear.